Financing Rapid Onset Natural Disaster Losses in India : A Risk Management Approach - World Bank (Washington, DC, 2013)
Twenty-two of India's 31 states are regarded as particularly prone to natural disasters: 55% of its land is vulnerable to earthquake, 8% is vulnerable to cyclone, and 5% is vulnerable to flood. In light of India's vulnerability to growing losses due to natural disasters and escalating fiscal pressures at the central and state levels, the World Bank undertook a detailed review of India's catastrophe exposures. The goal of this project was to examine loss potentials from rapid onset natural disasters and to consider the opportunity to apply enhanced country and state level risk management techniques, with a particular emphasis on the financing of post disaster reconstruction and the efficient allocation of public funds. The country risk management approach is based partly on corporate risk management principles, but accounts for key economic and social metrics such as government fiscal profiles and the living conditions of the poor. The first step under this methodology is to assess the potential losses from natural hazards on a probabilistic basis, and detailed studies were carried out in four states. The next step involves a formal and structured approach to understand the funding of natural calamity losses and identify the "natural disasters funding gap," which is the difference between the expected fiscal cost of an event and available ex post sources of government revenue. The study concludes that India still adopts a primarily reactive, or coping, approach to dealing with natural disasters. The current program, particularly at the national level, lacks institutional incentives and underplays the role of risk financing through ex ante mechanisms such as catastrophe reinsurance and contingent credit facilities. The development of ex ante funding programs is particularly critical because these programs typically serve as a primary source of immediate liquidity that would reduce human suffering, economic loss, and fiscal pressures in the aftermath of a natural disaster, and kick-start economic recovery. Ex ante funding approaches can also foster mitigation and provide incentives for institutional capacity building.